Exogenous treatment with salicylic acid alleviating copper toxicity in bean seedlings - Zengin, Fikriye (Springer India, 2014)
The present study was carried out to examine the effects of salicylic acid (SA) on growth and some physiobiochemical attributes in bean (Phaseolus vulgaris L.) plants exposed to copper stress. Exposure to copper significantly decreased root and shoot growth, chlorophyll and protein but increased malondialdehyde (MDA), carotenoid and proline. Exogenous application of SA acid was found to alleviate negative effects generated by heavy metals like copper in plant. Salicylic acid significantly increased root and shoot growth, chlorophyll and protein. In addition SA reduced the proline, MDA and carotenoid in copper stressed plants. The data suggest that the useful effect of SA during an earlier growth period could be related to avoidance of damage caused by exposure to copper. In addition, exogenous SA may improve the tolerance of the plant to the copper toxicity. © 2014 The National Academy of Sciences, India.
Keywords: Carotenoid; Chlorophyll; Copper; Malondialdehyde; Proline and salicylic acid